The Kv7 Modulator, Retigabine, is an Efficacious Antiseizure Drug for Delayed Treatment of Organophosphate-induced Status Epilepticus. (21st May 2021) - Barker, Bryan S.; Spampanato, Jay; McCarren, Hilary S.; Berger, Kyle; Jackson, Cecelia E.; Yeung, David T.; Dudek, F. Edward; McDonough, John H.
Highlights: The Kv 7 channel agonist retigabine is a novel treatment option for OP-induced SE. Retigabine with and without MDZ, attenuated electrographic seizure activity The combination therapy of retigabine and MDZ provided moderate neuroprotection. Abstract: Benzodiazepines are the primary treatment option for organophosphate (OP)-induced status epilepticus (SE), but these antiseizure drugs (ASDs) lose efficacy as treatment is delayed. In the event of a mass civilian or military exposure, significant treatment delays are likely. New ASDs that combat benzodiazepine-resistant, OP-induced SE are critically needed, particularly if they can be efficacious after a long treatment delay. This study evaluated the efficacy of the Kv 7 channel modulator, retigabine, as a novel therapy for OP-induced SE. Adult, male rats were exposed to soman or diisopropyl fluorophosphate (DFP) to elicit SE and monitored by electroencephalogram (EEG) recording. Retigabine was administered alone or adjunctive to midazolam (MDZ) at delays of 20- or 40-min in the soman model, and 60-min in the DFP model. Following EEG recordings, rats were euthanized and brain tissue was collected for Fluoro-Jade B (FJB) staining to quantify neuronal death. In the DFP model, MDZ + 15 mg/kg retigabine suppressed seizure activity and was neuroprotective. In the soman model, MDZ + 30 mg/kg retigabine suppressed seizures at 20- and 40-min delays. Without MDZ, 15 mg/kg retigabine provided partial antiseizure and neuroprotectant efficacy in the DFP model, while 30 mg/kg without MDZ failed to attenuate soman-induced SE. At 60 mg/kg, retigabine without MDZ strongly reduced seizure activity and neuronal degeneration against soman-induce SE. This study demonstrates the antiseizure and neuroprotective efficacy of retigabine against OP-induced SE. Our data suggest retigabine could be a useful adjunct to standard-of-care and has potential for use in the absence of MDZ.